2018
DOI: 10.21836/pem20180102
|View full text |Cite
|
Sign up to set email alerts
|

Immunocastration in donkeys: clinical and physiological aspects

Abstract: The work was aimed to evaluate testicular alterations induced by administration of immunocastration vaccine in Donkeys. A total of 12 adult Donkeys from the Northeast breed of Brazil were randomly distributed into control group (CG; n = 04) and immunocastration group (IG; n = 08). Donkeys from IG received two doses of Bopriva ® administered in an 30-day interval (Days 0 and 30). Blood samples were collected for testosterone dosage in this 30-day interval, when donkeys were weighted and measured for testicular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
1
5
2
Order By: Relevance
“…However, the period of testosterone suppression in that study was more extended (5-6 months) than 16 weeks in this study. In stallion donkeys receiving the different brand of GnRH vaccine at 400 µg twice, serum testosterone decreased at day 60 after the first vaccination, and remained at a low level until the end of the study at day 120 [25], similar to the duration of testosterone suppression of stallion mules in this study. It was unknown whether the serum testosterone of stallion donkeys beyond 120 days would be maintained at a low level or rise in the similar pattern as mules in this study.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…However, the period of testosterone suppression in that study was more extended (5-6 months) than 16 weeks in this study. In stallion donkeys receiving the different brand of GnRH vaccine at 400 µg twice, serum testosterone decreased at day 60 after the first vaccination, and remained at a low level until the end of the study at day 120 [25], similar to the duration of testosterone suppression of stallion mules in this study. It was unknown whether the serum testosterone of stallion donkeys beyond 120 days would be maintained at a low level or rise in the similar pattern as mules in this study.…”
Section: Discussionsupporting
confidence: 78%
“…Mares receiving high dose of the GnRH vaccine (Improvac) at 400 µg had no injecting site swelling after primary vaccination but 10.9% developed visible swelling, and 3.6% developed visible swelling accompanied by lameness after the second vaccination [35]. Donkeys did not develop any clinical adverse effects even receiving high dose of the GnRH vaccine at 400 µg twice [25], although the brand of vaccine in that study was different from the one using in our study. Other composition of chemicals and adjuvants within different brands of vaccine might contribute to the occurrence of clinical adverse effects.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…This is probably due to differences in the age and the larger size of the donkeys considered in the present study (140-250 vs. 400-450 kg). On the other hand, the mean value testis volume of donkeys obtained in this study is higher than that reported in the northeast Brazilian breed of donkeys (Rocha et al, 2018). The values of morphometric of the testicular parenchyma vary considerably among breeds, probably reflecting the spermatogenic activity for each breed.…”
Section: Discussioncontrasting
confidence: 77%
“…The maintenance of donkeys in farms or breeding centers is not common around the world, as the majority of the population regularly rears these equids without much interest (Rocha et al 2018). This situation has made it difficult to characterize various blood biomarkers, which are important for the understanding of health and disease states of these animals.…”
Section: Introductionmentioning
confidence: 99%